Introducing waqf based takaful model in India - Htay, Sheila Nu Nu; Syed, Ahmed Salman (2013)
Waqf is a unique feature of the socioeconomic system of Islam in a multi- religious and developing country like India. India is a rich country with waqf assets and the history of waqf in India can be traced back to 800 years ago. Most of the researchers, suggest how waqf can be used a tool to mitigate the poverty of Muslims. India has the third highest Muslim population after Indonesia and Pakistan. However, the majority of Muslims belong to the low income group and they are in need of help. It is believed that waqf can be utilized for the betterment of Indian Muslim community. Among the available uses of waqf assets, this paper focuses on how waqf can help Indian poor Muslims through takaful. Therefore, this paper is proposing to introduce waqf based takaful model in India. In addition, how this proposed model can be adopted in India is highlighted. It is believed that this proposal will be the interests of Muslim community, insurance operators and regulators